Genome-Wide Identification and Functional Analysis of the Calcineurin B-like Protein and Calcineurin B-like Protein-Interacting Protein Kinase Gene Families in Turnip (Brassica rapa var. rapa) - Yin, Xin; Wang, Qiuli; Chen, Qian; Xiang, Nan; Yang, Yunqiang; Yang, Yongping (Frontiers in Plant Science, 2017)
The calcineurin B-like protein (CBL)–CBL-interacting protein kinase (CIPK) complex has been identified as a primary component in calcium sensors that perceives various stress signals. Turnip (Brassica rapa var. rapa) has been widely cultivated in the Qinghai–Tibet Plateau for a century as a food crop of worldwide economic significance. These CBL–CIPK complexes have been demonstrated to play crucial roles in plant response to various environmental stresses. However, no report is available on the genome-wide characterization of these two gene families in turnip. In the present study, 19 and 51 members of the BrrCBL and BrrCIPK genes, respectively, are first identified in turnip and phylogenetically grouped into three and two distinct clusters, respectively. The expansion of these two gene families is mainly attributable to segmental duplication. Moreover, the differences in expression patterns in quantitative real-time PCR, as well as interaction profiles in the yeast two-hybrid assay, suggest the functional divergence of paralog genes during long-term evolution in turnip. Overexpressing and complement lines in Arabidopsis reveal that BrrCBL9.2 improves, but BrrCBL9.1 does not affect, salt tolerance in Arabidopsis. Thus, the expansion of the BrrCBL and BrrCIPK gene families enables the functional differentiation and evolution of some new gene functions of paralog genes. These paralog genes then play prominent roles in turnip's adaptation to the adverse environment of the Qinghai–Tibet Plateau. Overall, the study results contribute to our understanding of the functions of the CBL–CIPK complex and provide basis for selecting appropriate genes for the in-depth functional studies of BrrCBL–BrrCIPK in turnip.